Imaging Findings of Congenital Glaucoma in Opitz Syndrome - Choudhary, A.K. (AJNR Am J Neuroradiol, 2008)
SUMMARY: Opitz syndrome is a rare autosomal recessive disorder of cholesterol metabolism associated with mental retardation and multiple congenital malformations. It is also uncommonly associated with congenital glaucoma. We describe the orbital findings on CT in this rare case of a patient with Opitz syndrome who presented with congenital glaucoma, with a review of the literature. The CT findings of congenital glaucoma, which have not been described before in the literature, are also discussed. It is important for the radiologist to be aware of this rare association. It is also important to be aware of the findings of congenital glaucoma on CT because patients with Opitz syndrome and other syndromes associated with learning difficulties may not present with typical clinical features of glaucoma. A high index of suspicion will lead to a correct diagnosis and earlier intervention.